A conceptual framework of the service delivery system design for hospitality firms in the (post-)viral world: The role of service robots. (October 2020) - Seyitoğlu, Faruk; Ivanov, Stanislav
Highlights: Provides a conceptual framework of the service delivery system design for hospitality firms in the (post-)viral world. Identifies three service delivery system designs (robotic, human-based, and mixed). Analyses the requirements, (dis)advantages, and potential target markets of suggested systems. In a physically distant service the physical contact between the service provider and the customer is eliminated. Abstract: This study aims to develop a conceptual framework of the service delivery system design for hospitality firms in the (post-)viral world. Several theoretical approaches such as resource-based view, value chain analysis, stakeholder theory, PESTEL analysis, positioning strategy, and service delivery system design were adopted. The paper identified three service delivery system designs (robotic, human-based, and mixed) and analyses their requirements, advantages, disadvantages, and potential target markets. According to the suggested model, hospitality firms need first to explore the expectations of tourists. Then comes the analysis phase (based on a holistic perspective, and consisting of RBV, Value chain, Stakeholder, and PESTEL analyses), which helps hospitality firms to identify how they should differentiate and position themselves in the market. Following, companies decide on what kind of service delivery system they should offer to their target customers, and position themselves in the market according to the chosen system.